Control rod position measurement with helix-electrode capacitance sensor in nuclear heating reactor. (October 2018) - Hu, Guang; Qin, Benke; Bo, Hanliang
Highlights: A new device is designed to measure the ungrounded/grounded control rod positions in NHR. The FEM and electric model were set up with ungrounded/grounded control rod for the helix-electrode sensor. The subsequent quantitative analyses on the data indicate the high reliability and accuracy of the apparatus for monitoring rod position in NHR. Abstract: Capacitance sensors are frequently applied for dielectric objects measurements. However, the study on the ungrounded/grounded control rod position measurements with capacitance sensor is limited. In this connection, a system based on the helix-electrode capacitance sensor is applied to measure the rod position in NHR. Based on the variations of equivalent electrical permittivity with different control rod positions in NHR, the helix-electrode capacitance sensor has been successfully used for the ungrounded/grounded control rod position measurement due to its advantages of non-invasion, low-cost, high reliability and non-radiation. The finite element method is used to calculate the sensor capacitance and the sensor sensitivity is also presented. Then, the ungrounded/grounded control rod position experiment is carried out to measure the response of the helix-electrode capacitance sensor, in which a novel method is proposed to calibrate the helix-electrode capacitance sensor based on the grating linear displacement measuring probe. The capacitances obtained by simulations were compared with experiment results to verify the proposed models. The subsequent quantitative analyses on the data indicate the reliability and accuracy of the apparatus for monitoring control rod position. It is demonstrated that such a system shows promising applications for measurements of the control rod position in NHR.